The rise and fall of social housing? Housing decommodification in long-run perspective - Konstantin A. Kholodilin; Sebastian Kohl; Florian Müller (Max Planck Institute for the Study of Societies, 2022)
The comparative study of housing decommodification lags behind classical welfare state research, while housing research itself is rich in homeownership studies but lacks comparative accounts of private and social rentals due to missing comparative data. Building on existing works and various primary sources, this study presents a new collection of up to forty-eight countries' social housing shares in stock and new construction since the first housing laws around 1900. The interpolated benchmark time series generally describe the rise and fall of social housing across a residual, a socialist, and a Northern-European housing group. The decline was steeper than for the classical welfare state, but the degree of erosion was surprisingly small in some countries where public housing associations remained resilient. Within the broader housing welfare state, social housing correlates positively with rent regulation and allowances, but negatively with homeownership subsidies and liberal mortgage regulation. A multivariate analysis shows that social housing is rather explained by housing shortages and complementarities with rental and welfare policies than by typical welfare state theories (GDP, political parties). Generally, the paper shows that conventional housing typologies are difficult to defend over time and argues more generally for including housing decommodification in welfare state research. – – Die vergleichende Forschung zur Dekommodifizierung des Gutes Wohnen ist bisher von der klassischen Wohlfahrtsstaatsforschung vernachlässigt worden. Die Wohnungsforschung selbst ist wiederum reich an Studien zum Wohneigentum, aber vergleichende Darstellungen zu privaten und sozialen Mietwohnungen sind aufgrund fehlender komparativer Daten wenig erforscht. Aufbauend auf bestehenden Arbeiten und verschiedenen Primärquellen stellt diese Studie daher zunächst eine neue Datensammlung von bis zu 48 Ländern vor, die den Anteil der Sozialwohnungen an den Beständen und Neubauten seit den ersten Wohnungsbaugesetzen um 1900 erfasst. Die interpolierten Benchmark-Zeitreihen beschreiben im Allgemeinen den Aufstieg und Fall des sozialen Wohnungsbaus in einem residualen, sozialistischen und einem nordeuropäischen Wohnungsregime. Der Rückgang war steiler als beim klassischen Wohlfahrtsstaat, aber überraschend resilient in Ländern mit öffentlichen Wohnungsbaugesellschaften. Innerhalb des umfassenderen Wohnungswohlfahrtsstaates korreliert der soziale Wohnungsbau positiv mit der Regulierung von Mieten und Wohngeldzahlungen, aber negativ mit Wohneigentumssubventionen und liberalen Hypothekenregelungen. Eine multivariate Analyse zeigt, dass der soziale Wohnungsbau eher durch Wohnungsknappheit und funktionale Komplementarität mit Miet- und Sozialpolitik als mit typischen wohlfahrtsstaatlichen Faktoren (BIP, politische Parteien) erklärt wird. Generell zeigt der Beitrag, dass herkömmliche Wohnungstypologien im Laufe der Zeit nur schwer zu verteidigen sind, und plädiert dafür, die Dekommodifizierung von Wohnraum stärker in die Wohlfahrtsstaatsforschung einzubeziehen.
hdl:21.11116/0000-000A-DA29-3
Keywords: 300; housing tenure; social housing; welfare state; Sozialwohnungsbau; Wohlfahrtsstaat; Wohneigentumsformen